Comparison of the Effects of Indobufen and Aspirin in Older Patients with Coronary Artery Disease After Coronary Drug-Eluting Stent Implantation: A Prospective Randomized Single-Center Study - Yeshun Wu MD; Zhenyan Gao MD; Qizhi Jin MD; Jiasheng Zheng MD; Hongqing Xu MD; Xiaoming Tu MD (Clinical and Applied Thrombosis/Hemostasis)
After coronary drug-eluting stent (DES) implantation, dual antiplatelet therapy (DAPT, usually aspirin in combination with a P2Y12 inhibitor) is necessary. However, older patients are prone to aspirin intolerance or resistance. Indobufen has been reported as an ideal alternative to aspirin. To evaluate the clinical efficacy and safety of indobufen-based DAPT in this population, a total of 251 older patients (aged ≥65 years) undergoing coronary DES implantation in a tertiary healthcare facility in Quzhou, China, were enrolled, of which 110 received indobufen-based DAPT and 141 received aspirin-based DAPT. Baseline data, adverse reactions, adverse events, angina attacks, and repeated revascularization during 1-year follow-up were collected. At 1-year follow-up, creatinine, and left ventricular ejection fraction levels in the indobufen group were higher than those in the aspirin group, whereas estimated glomerular filtration rate levels were lower than those in the aspirin group. No significant difference in the incidence of adverse reactions or adverse events was found between the two groups. At 1-year follow-up, the incidence of angina in the indobufen group was significantly lower than that in the aspirin group, and the repeated revascularization rate was lower than that in the aspirin group. Indobufen-based DAPT was beneficial in avoiding repeated revascularizations (odds ratio 0.433, 95% CI 0.229-0.821, P  = 0.010). These findings highlight that, for older patients who underwent coronary DES implantation, indobufen-based DAPT may be a better choice, which can effectively improve patients’ symptoms and prognosis. However, application to older patients with potential renal insufficiency requires caution.